Ethical norms in the old and new testament: Jesus is the source of Christian ethics - Ferreira, Edileuza Barros; Nascimento, Oslei do; Mildenberg, Emerson; Almeida, Sérgio Antunes de (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Teologia, 2022)
Through the teachings of Jesus, he alerts man to conquer the transcendental values of the spirit. An avant-garde view of the gospel of Christ, revealing how current ethics presented more than two thousand years ago. Through timely and modern reflections, it allows for a better understanding of the essence of the lessons that the carpenter from Nazareth brought to the universe. From the biblical accounts, it appears that Jesus' ethics was based on defending the dignity of all human beings. Jesus did not inaugurate a moral code to condemn the impure and sinners. The ethics of Christ has its foundation in the care of life, with humanization. We will find in the Bible theoretical principles that govern different areas of human life. It is in the interaction with these principles and with the problems of each generation that Christian ethics is contextualized and updated, without ever abandoning the permanent and transcendent values revealed in the Scriptures. Christian ethics, in short, is the set of moral values totally and solely based on the Holy Scriptures, by which man must regulate his conduct in this world, before God, his neighbor and himself. It is not a set of rules by which men can come to God - but it is the standard of conduct by which they can please the God who has already redeemed them. Being based on divine revelation, believing in absolute moral values, which are the will of God for all men, of all cultures and at all times.